A quantitative study on clinical performance factors among nursing students in a Malaysian teaching hospital - Abdul Hamid, Siti Hazariah; Lee, Siew Pien; Idrus, Nurul Hanis; Abd Rashid, Norlinda; Ellin, Mohammed Rasheedan (Universiti Putra Malaysia, 2025)
Introduction: Nursing students frequently struggle with insufficient faculty support, inadequate clinical environ- ments, and personal challenges, which significantly hinder their clinical performance. Addressing these barriers through improved communication, enhanced support structures, and better clinical settings is essential to optimize their learning and professional growth. Method: This cross-sectional study used a questionnaire to assess socio-de- mographic data and performance-influencing factors such as student traits, Clinical Nursing Instructor (CNIs) influ- ence, and clinical ward ambiance through convenience sampling. Data was analyzed using SPSS version 20. Re- sults: Chi-square analysis showed that significant barriers to effective clinical performance include students’ lack of confidence, practice, communication with staff nurses, anxiety, and exhaustion. Inadequate clinical environments, such as a shortage of CNIs and their negative attitudes, also impeded performance. Younger students and those in earlier years reported more anxiety due to inexperience and fear of errors. Additionally, students felt exhausted from balancing clinical placements with theory classes. Conclusion: Addressing these challenges necessitates concerted efforts to enhance collaboration and communication between nursing educators and ward staff, thus optimizing students’ clinical performance.